Seductive subsidies? An analysis of second-degree moral hazard in the context of photovoltaic solar systems - Evert Reins (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
This paper studies how subsidies for photovoltaic solar systems can lead to second-degree moral hazard - the impulse of installers to increase factors determining the total subsidies and/or transaction when consumers receive larger subsidy levels. Employing an instrumental variable strategy using plausibly exogenous variation in the size of subsidy levels to address concerns about self-selection of installers into specific subsidy levels, I quantify the impact of subsidy levels on the expected electricity output and transaction prices of PV systems in California. The results are consistent with hypothesized drivers of second-degree moral hazard as larger subsidy levels are associated with i) an increased measure of the expected electricity output leading to increased subsidies when third-parties own the PV system and ii) increased transaction prices when consumers themselves own the system. The results further suggest that subsidy programs should verify the work of an installer, for example during mandatory field inspections, as these reduce second-degree moral hazard.
Keywords: H23; H32; H76; D82; Q42; C26; 330; PV systems; Credence goods; Subsidies; Asymmetric information; Second-degree moral hazard